Science, power and regimes of truth in access to teaching profession academic texts - Monarca, Héctor (Education Policy Analysis Archives, 2021)
The objective of this work is to highlight the performative-ideological effects of scientific discourses, in this case, through the analysis of academic texts published in Spain on a very specific subject: “selective processes for access to teaching work” in public educational system. Epistemologically, it starts from the assumption that the social sciences in general and the educational sciences in particular have been related from historical processes of production and reproduction of the social order. Therefore, assuming the Bourdiean perspective, science is addressed in this work as a field of power that assumes explicitly and implicitly various assumptions regarding the world. Methodologically it is a review article from a historical-dialectical-critical perspective. In this way, the texts are analyzed as an expression of diverse interests and positions that are part of disputes related to the educational field in particular or to the social order in general, the instituted, “the political” in the sense of Castoriadis (1996), evidencing a political praxis.